2023
DOI: 10.3389/fbioe.2023.1170212
|View full text |Cite
|
Sign up to set email alerts
|

Photo-crosslinked adhesive hydrogel loaded with extracellular vesicles promoting hemostasis and liver regeneration

Abstract: Hepatectomy is an effective surgical method for the treatment of liver diseases, but intraoperative bleeding and postoperative liver function recovery are still key issues. This study aims to develop a composite hydrogel dressing with excellent hemostatic properties, biocompatibility, and ability to promote liver cell regeneration. The modified gelatin matrix (GelMA, 10%) was mixed with equal volumes of sodium alginate-dopamine (Alg-DA) at concentrations of 0.5%, 1%, and 2%. Then a cross-linking agent (0.1%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Moreover, we are confident that the swelling, biodegradability, and hemolysis characteristics are in line with the ones measured and described by Xia et al The authors demonstrated a hemolysis rate of less than 5%, which indicates good blood compatibility. GelMA alone showed a swelling rate of around 18% and a remaining mass of roughly 4.5% over the course of 21 days [ 40 ]. However, combining GelMA with alginate did result in a significantly more stable construct with a remaining mass of circa 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we are confident that the swelling, biodegradability, and hemolysis characteristics are in line with the ones measured and described by Xia et al The authors demonstrated a hemolysis rate of less than 5%, which indicates good blood compatibility. GelMA alone showed a swelling rate of around 18% and a remaining mass of roughly 4.5% over the course of 21 days [ 40 ]. However, combining GelMA with alginate did result in a significantly more stable construct with a remaining mass of circa 20%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bleeding time (all data were shown as mean ± standard deviation, n = 4) was greater than 200 s in the control group, whereas in the hydrogel group it was less than 100 s. Also, no significant post-operative adhesions were seen in the experimental group compared to the control group. Wu et al 112 developed a composite hydrogel encapsulating MSCs-exos, which in addition to having good biocompatibility and hemostatic properties, encouraged hepatocyte proliferation by releasing exosomes. Thus, injectable hydrogels serve as potential new modalities for liver regeneration after hepatectomy.…”
Section: Hydrogel Encapsulated Msc/exosomes In Liver Injurymentioning
confidence: 99%
“…132 Furthermore, GelMA is an extracellular matrix (ECM)-like hydrogel material due to the incorporation of the arginine–glycine–aspartate (RGD) sequence and matrix metalloproteinase (MMP) motifs, which stimulates cell adhesion and proliferation. 133 Xia et al 112 designed a photo-crosslinked hydrogel loaded with exosomes composed of GelMA, dopamine-modified alginate (Alg-DA), and exos (GelMA/Alg-DA/Exo). The hydrogel was applied after hepatectomy and demonstrated good adhesion and biocompatibility, and effective haemostasis while also promoting hepatocyte regeneration.…”
Section: Preparation Of Hydrogel In Liver Injurymentioning
confidence: 99%
“…developed a photo‐crosslinked adhesive HG containing GelMA and sodium alginate‐dopamine for regional delivery of adipose MSC‐derived sEVs. [ 156 ] The sEV‐embedding composite HG increased blood coagulation indices and improved the cell proliferation and migration of LO2 hepatocytes, thereby simultaneously promoting liver wound hemostasis and liver regeneration.…”
Section: General Surgery and Biomaterial‐assisted Sc‐sev Therapymentioning
confidence: 99%